Implementation of Tawhidi String Relations (TSR) in Demand, Supply, Elasticity, and Market Equilibrium - Arnoldy Arnoldy; Tatik Mariyanti (Indonesian Journal of Business, Accounting and Management (IJBAM), 2021)
This study intends to explore the implementation of Tawhidi String Relations (TSR) in demand, supply, elasticity, and market equilibrium and the impact of implementing the TSR approach in these functions. Tawhidi String Relations (TSR), a methodology derived from Tawhid that uses the Al-Quran and Sunnah as an ontology in each solution variable with the ultimate goal of achieving social wellbeing. This TSR method has the advantage of a process of interaction, integration, and evolution which is understood as the evolution of the formation of human knowledge that is subject to Divine Laws through a shuratic process and ijma’, thus realizing a universal social wellbeing function. This study uses qualitative research methods by exploring through literature studies. Basically, demand, supply, elasticity, and market equilibrium in conventional economics have several differences with those found in Islamic economics where what distinguishes them is demand, supply, elasticity and market equilibrium in Islamic economics has limitations and principles that must be met by individuals to behave accordance with Islamic law which is based on the Al-Quran, Sunnah, Ijma', and Qiyas as the agreed source of Islamic law.